Trabajo en equipo y calidad del cuidado de Enfermería al paciente hospitalizado. Hospital de Apoyo Chepén - 2009 - Barba Ahumada, Delia Karina (2009)
This descriptive correlational study and cutting cross was made with the nurses and patients hospitalized in the Hospital de Apoyo Chepén during 2009, in order to determine the relationship of teamwork and quality of nursing care. The sample consisted of 40 persons of the nursing staff and 40 patients hospitalized in different departments used two instruments were previously validated. The findings show that the level of teamwork was referred to as regular by 62.5 percent as good by 22.5 percent and poor by 15.0 percent. Regarding the level of Nursing Care Quality 82.5 percent of patients referred him as deficient, the 12.50 per cent as fair and 7.50 per cent as good. The statistical test reports that there is highly significant (p <0.05) between the level of teamwork and the quality of nursing care to hospitalized patients in the Hospital Support Chepén 2009. There is a highly significant difference (p <0.001) between the proportion of the levels of teamwork and quality of care matching the 62.5 percent for the former and 82.5 percent for the second respectively.